Customary Forests Social Forestry Scheme: One Of The Strengthening Of Indigenous Peoples In Managing Natural Resources - Muhammad, Ari; Adha, Muhammad Yogie (JURNAL HUKUM SEHASEN, 2025)
Although the 1945 Constitution of the Republic of Indonesia states that the state recognizes and respects customary law communities, its recognition is conditional on customary law communities in managing their natural resources, especially in the status of certain forest areas. This paper examines how the role of customary forests in social forestry schemes provides space and access to customary law communities in natural resource management. The results of the study show that the ratification of the Decree (SK) of Customary Forests in the social forestry scheme is able to provide legitimacy to indigenous peoples in managing natural resources in accordance with their local wisdom and also have an impact on strengthening customary practices in the management of their natural resources